Accountant's Desk Handbook (Book). - Thacker, Ronald J.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Accountant's Desk Handbook," 2nd ed., by Albert P. Ameiss and Nicholas A. Kargas.